THEORETICAL CONCEPT OF CREDIT RISK MANAGEMENT - Dragosavac, Miloš M (International Journal of Economic Practice and Policy, 2014)
With the development of the banking business and the economy, exposure to different types of risk becomes greater. Identifying all risks and adequate measures have become an extremely important factor in business success in the increasingly complex economic conditions. Risks in business, in the last ten years have become the burning issue in debates among the scientific experts. With the aim of stable development of its business and equal participation in a large competitive market, primarily in order to protect its depositors and preserve system stability and liquidity, banks have to incorporate into their strategic goals the strategies of banking risks. Credit risk is of great value within the overall risks that accompany the business activity of banks, economy, and other forms of business organization. Its nature and presence in all segments of the business activities speak enough about its importance and the need for its management. Permanently growing trend of credit risk is a reality faced by not only the banking organization, but also the subjects in the economic and non-economic sector, which makes the issue of credit risk extremely important and relevant. The subject of this paper is a theoretical analysis of credit risk in banking business. Banking operations are increasingly exposed to credit risk, which indicates the inability of banks to settle their claims based on previously approved loans, and this is the case-in-point for this specific research subject.